2011
DOI: 10.1103/physreve.84.041136
|View full text |Cite
|
Sign up to set email alerts
|

Gaussian model of explosive percolation in three and higher dimensions

Abstract: The Gaussian model of discontinuous percolation, recently introduced by Araújo and Herrmann [Phys. Rev. Lett., 105, 035701 (2010)], is numerically investigated in three dimensions, disclosing a discontinuous transition. For the simple-cubic lattice, in the thermodynamic limit, we report a finite jump of the order parameter, J = 0.415 ± 0.005. The largest cluster at the threshold is compact, but its external perimeter is fractal with fractal dimension dA = 2.5 ± 0.2. The study is extended to hypercubic lattice… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
51
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 60 publications
11
51
0
Order By: Relevance
“…It is the local optimization rule that leads to continuity of the explosive percolation transition in these models. In more exotic models employing various global optimization algorithms and their variations, discontinuities may occur [28][29][30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…It is the local optimization rule that leads to continuity of the explosive percolation transition in these models. In more exotic models employing various global optimization algorithms and their variations, discontinuities may occur [28][29][30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Besides the Achlioptas process, many new models such as cluster aggregation model [15][16][17], Gaussian model [18,19], Hamiltonian approach [20] have been devised and studied, showing that discontinuous transition can be made when the evolution mechanism produces many clusters which are relatively large in the subcritical regime [21]. Although some numerical [22][23][24][25] and theoretical results [26] demonstrated that explosive percolation in the original Achlioptas processes is actually continuous in the mean-field limit, discontinuous transition indeed exists in other alternative models, e.g., the global competitive percolation process [27,28].…”
mentioning
confidence: 99%
“…Among others [14][15][16][17][18][19], a model called spanning cluster avoiding (SCA) was introduced [20] aiming to generate a DPT. The DPT of the SCA model is rather trivial, for the percolation threshold is placed at p c = 1 in the thermodynamic limit, but for finite-sized systems p c < 1.…”
mentioning
confidence: 99%